miR-214 Modulates the Growth and Migration of Oral Cancer before and after Chemotherapy through Mediating ULK1 - Yongtao Yang; Xiaolan Sun; Minghua Li; Limei Li; Shanshan Wang; Yaomin Zhu (Journal of Immunology Research)
The role of miRNAs as crucial components in carcinogenesis has been well documented. However, whether and how miR-214 influences oral cancer cells’ drug resistance remains to be elucidated, and its downstream targets are still under investigation. Hence, this research is aimed at determining miR-214 and ULK1 expression in oral cancer before and after chemotherapy and their correlations with cancer cell growth. Human oral normal epithelial cells and human tongue squamous cell carcinoma CAL-27 cells were cultured to detect miR-214 and ULK1 levels. It was found that before chemotherapy, miR-214 was higher, while ULK1 was underexpressed in CAL-27 cells, versus normal epithelial cells. After chemotherapy, miR-214 decreased obviously in CAL-27 cells, while ULK1 level increased significantly. In addition, autophagy-related genes (Beclin 1, mTOR, and P53) in CAL-27 cells were found to be significantly inhibited before chemotherapy and were obviously increased after chemotherapy. Moreover, to further determine the impacts of miR-214 and ULK1 on oral cancer cell growth after chemotherapy, the two were overexpressed or silenced in CAL-27 cells after transfection. We found that ULK1 could effectively decrease the activity and invasion of CAL-27 cells and increase their apoptosis level, while miR-214 could antagonize its antitumor effect. Therefore, miR-214 can be used as an early prognostic biomarker for oral cancer, and ULK1 is a new candidate therapeutic target.